2020
DOI: 10.3389/fimmu.2020.531491
|View full text |Cite
|
Sign up to set email alerts
|

IDO Expression in Cancer: Different Compartment, Different Functionality?

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) is a cytosolic haem-containing enzyme involved in the degradation of tryptophan to kynurenine. Although initially thought to be solely implicated in the modulation of innate immune responses during infection, subsequent discoveries demonstrated IDO1 as a mechanism of acquired immune tolerance. In cancer, IDO1 expression/activity has been observed in tumor cells as well as in the tumor-surrounding stroma, which is composed of endothelial cells, immune cells, fibroblasts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 223 publications
(264 reference statements)
3
105
0
1
Order By: Relevance
“…Analysis of monocytic (M; CD14 + HLA-DR − ) and granulocytic (G; CD33 + CD14 − HLA-DR − ) MDSC demonstrated that IDO1 transcript level was higher in M-MDSC than in G(PMN)-MDSC (SI Appendix, Fig. S6), consistent with publications indicating M-MDSC as a main source of IDO expression in murine tumor models (46,47). Furthermore, IDO1 expression was strongly associated with the expression of genes in the Regulation of ROS category, notably showing a positive correlation with the expression of SIRT1 and HIF1, cellular redox and oxygen sensors (48) and a negative correlation with ROS regulators (e.g., SOD1, GSTP1, CAT, NOXA1, and MPO) (49).…”
Section: Ros Scavenging Reverses the Aberrations Of Ido1-deficient Mysupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of monocytic (M; CD14 + HLA-DR − ) and granulocytic (G; CD33 + CD14 − HLA-DR − ) MDSC demonstrated that IDO1 transcript level was higher in M-MDSC than in G(PMN)-MDSC (SI Appendix, Fig. S6), consistent with publications indicating M-MDSC as a main source of IDO expression in murine tumor models (46,47). Furthermore, IDO1 expression was strongly associated with the expression of genes in the Regulation of ROS category, notably showing a positive correlation with the expression of SIRT1 and HIF1, cellular redox and oxygen sensors (48) and a negative correlation with ROS regulators (e.g., SOD1, GSTP1, CAT, NOXA1, and MPO) (49).…”
Section: Ros Scavenging Reverses the Aberrations Of Ido1-deficient Mysupporting
confidence: 86%
“…IDO1 is unique in that it utilizes superoxide anion radicals as both a cofactor and a substrate ( 32 ) and is also reported to have peroxygenase activity, thereby consuming peroxide ( 58 ). IDO-1 is up-regulated in Ly6C hi M-MDSCs ( 46 , 47 ) ( SI Appendix , Fig. S6 ), which are susceptible to ROS levels and show expedited differentiation into neutrophils in the presence of ROS elevation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indoleamine 2,3-dioxygenase (IDO), which is frequently upregulated in various types of cancer, is also known to regulate tumor dormancy. IDO is a cytosolic heme-containing enzyme that degrades tryptophan (which is essential for maintaining physiological and immunological homeostasis) into kynurenine, which triggers G0/G1 cell cycle arrest [ 50 ]. Kynurenine also activates a cytosolic transcription factor, aryl hydrocarbon receptor (AhR), followed by the upregulation of IL-6 to maintain IDO expression in an autocrine manner [ 51 ].…”
Section: Emt-induced Cscsmentioning
confidence: 99%
“…CSC-producing IDO degrades tryptophan into kynurenine, which activates the cytosolic transcription factor AhR that is widely expressed in immune cells [ 50 ]. The AhR activation not only suppresses cytotoxicity, proliferation, and survival of CTLs and NK cells, but also generates Tregs and MDSCs, resulting in impairment of anti-tumor immunity [ 58 , 83 ].…”
Section: Immune Supporters For Cancer Metastasismentioning
confidence: 99%
“…The overexpression of IDO1 is not merely a consequence of tumorigenesis but is seen as an early hallmark of inflammatory bowel disease and colitis indicating that it is in part driving tumorigenesis [161], [162], [162]- [164]. Loss of tumor suppressor gene bridging integrator 1 (BIN1) and overexpression of pro-inflammatory enzyme, COX-2 are also associated with an increased IDO1 expression, along with signals from pro-inflammatory cytokines, especially IFNγ [165]. IDO1 overexpression is also observed in colon cancer cell lines (HTC-116 and HT-29) in absence of an inflammatory environment, suggesting that genetic mutations or epigenetic modification of IDO1 could also be driving colon carcinogenesis [32], [166], [167].…”
Section: Therapeutic Targeting Of Indoleamine 23-dioxygenase (Ido1)mentioning
confidence: 99%